Podoconiosis, Epidemiology, Pathogenesis, Management, and Prevention Approaches with Special Focus in Ethiopia - Mahammed, Abas (International Journal of Pharmaceutical & Biological Archive, 2023)
Podoconiosis is a condition brought on by exposing one’s foot to irritable clay soil. The non-filarial endemic elephantiasis of the lower legs is hypothesized to be brought on by extended foot exposure to volcanic red clay soils. Poor agriculturalists frequently walk barefoot in the tropical highlands, which are a risk factor for exposure to irritating clay soil particles. The highlands of tropical Africa, Central America, and northwest India are typical locations for podoconiosis worldwide. African nations with a high prevalence of podoconiosis include Uganda, Tanzania, Kenya, Rwanda, Burundi, Sudan, and Ethiopia, according to data on the disease’s global distribution. Podoconiosis was most prevalent in the Amhara, Oromia, and Southern Nations, Nationalities, and People regional states in Ethiopia’s central highlands. Recent mapping in Ethiopia revealed that six regional states Amhara, Benishangul Gumuz, Oromia, SNNPR, Somali, and Tigray have high rates of podoconiosis. Podoconiosis is a completely preventable tropical non-communicable disease. Since wearing footwear has become customary, it has been eliminated from nations in northern Africa and Europe. Podoconiosis elimination has been given priority by the Ethiopian Federal Ministry of Health; however, the national program is struggling to stay on track for the goal.